Perbedaan Hasil Crossmatch Metode Gel dengan Waktu Inkubasi 5 Menit, 10 Menit, dan 15 Menit: Differences in Gel Method Crossmatch Results with Incubation Times of 5 Minutes, 10 Minutes, and 15 Minutes - KEKE PUTRI WULANSARI (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Crossmatch is an essential procedure in blood transfusion to ensure compatibility between donor and recipient blood and to prevent transfusion reactions. The gel method is widely used due to its high sensitivity and specificity, as well as its more objective result interpretation; however, the effectiveness of shorter incubation times still requires evaluation. This study aimed to determine the effect of incubation time variations on the results of gel method crossmatch examinations. This laboratory experimental study employed a one-group posttest-only design using 10 venous blood samples obtained from healthy respondents selected through purposive sampling. Gel method crossmatch examinations were performed using incubation times of 5 minutes, 10 minutes, and 15 minutes. Agglutination results were subsequently observed and analyzed. The results demonstrated that all samples (100%) showed negative agglutination across all incubation time variations, indicating no differences in crossmatch results among the three incubation durations. These findings suggest that variations in incubation time between 5 and 15 minutes do not influence the results of gel method crossmatch examinations in healthy populations. Therefore, the gel crossmatch method may be applied with shorter incubation times under specific conditions without compromising examination accuracy, potentially improving efficiency in blood transfusion services.